Real Dimensions of Binary Lectures in the Thematic Specialization “Gamification and Tools for Its Application” - Borislava Petrova; Lina Yordanova (Педагогически форум)
The modern teacher needs knowledge of methods that ensure the active participation of students in the learning process. Gamification has proven capabilities in this direction and is defined as one of the successful innovative teaching methods in the XXI century. The mastering of this method by the teachers is a subject of thematic specializations, which to one degree or another become for the participants an easily appreciable example of learning processorganization. This article shares experiment in organizing such specialization through co- teaching or binary lectures. The described model of co-teaching leads to effective training of teachers in the specialization according to the opinion of the teachers themselves, who over 50% work for the Center for Support of Children with Special Educational Needs (SEN).